Reduction in Serum LDL Cholesterol Using a Nutrient Compendium in Hyperlipidemic Adults Unable or Unwilling to Use Statin Therapy: A Double-Blind Randomized Crossover Clinical Trial. Issue 2 (26th January 2022) - Kopecky, Stephen L; Alias, Soumya; Klodas, Elizabeth; Jones, Peter J H
ABSTRACT: Background: Many hyperlipidemic patients prescribed β-hydroxy-β-methylglutaryl coenzyme A reductase inhibitors (statins) are unable or unwilling to take them. A hedonically acceptable snack-based solution formulated from cholesterol-lowering food ingredients could represent a therapeutic alternative but has not been tested in this population. Objectives: To evaluate the effect of snacks containing a compendium of functional bioactives on fasting LDL cholesterol in statin candidates unwilling to use or intolerant to ≥1 statin drug. Secondary outcomes included changes in circulating total cholesterol (TC), triglycerides, HDL cholesterol, fasting glucose, insulin, and high-sensitivity C-reactive protein concentrations, as well as effects of single-nucleotide polymorphisms (SNPs) on outcome. Methods: This multicenter, randomized, double-blind, free-living crossover study was composed of 2 regimented phases of 4 wk each, separated by a 4-wk washout. Eighteen men and 36 women, with a mean ± SD age of 49 ± 12 y and mean ± SD LDL cholesterol of 131 ± 32.1 mg/dL, were instructed to ingest a variety of ready-to-eat snacks twice daily as a substitute for something they were consuming already. Other behavior changes were actively discouraged. Treatment products provided ≥5 g fiber, 1000 mg ω-3 (n–3) fatty acids, 1000 mg phytosterols, and 1800 μmol antioxidants per serving. Control products were calorie-matched like-items drawn from the general grocery marketplace. Serum lipids were measured at baseline and the end of each phase and compared using the ANOVA model. Compliance to study foods was confirmed by serum 18:3n–3 concentration assessment. Results: Comparing intervention phase endpoints, LDL cholesterol was reduced a mean ± SD of 8.80 ± 1.69% ( P < 0.0001), and TC was reduced a mean ± SD of 5.08 ± 1.12% ( P < 0.0001) by treatment foods compared with control foods, whereas effects on other analytes did not differ between treatments. SNPs were not significantly related to outcomes ( P ≥ 0.230). Compliance with study foods was 95%. Conclusions: Consumption of hedonically acceptable snacks containing a compendium of cholesterol-lowering bioactive compounds can rapidly and meaningfully reduce LDL cholesterol in adult patients unable or unwilling to take statin drugs. This trial was registered at clinicaltrials.gov as NCT02341924.